Augmented reality in online retailing: a systematic review and research agenda. Issue 4 (6th September 2021) - Kumar, Harish
Abstract : Purpose: Augmented reality (AR) has received massive attention in online retail. Therefore, the paper aims to review the state-of-the-art literature on AR in online retailing, by identifying the antecedents, drives, outcomes, theoretical lenses, typology and methodological approaches. The study further aims to identify the critical avenues for future research. Design/methodology/approach: To advance the conceptual and managerial understanding of AR, the study synthesizes the literature through a systematic literature review approach by reviewing 53 articles. Findings: Several AR characteristics significantly influence utilitarian, hedonic, perceived risk and experiential value, ultimately resulting in a positive attitude, decision-making assistance and behavioural intentions, wherein customer experience (flow, spatial presence, mental imagery and immersion) plays a mediating role in the process. The study also lists the top authors, articles, journals, countries, theories and methodology used. Originality/value: The study provides a comprehensive framework on consumer behaviour towards AR in online retailing. Further, the study proposes the future research agenda in the social side of AR, the dark side of AR, customer engagement, use of AR for experiential value and AR marketing domain.